DISTRIBUTION OF KARNAL BUNT OF WHEAT IN PAKISTAN - BHUTTA, A. RAUF; AHMAD, SYED IRFAN (Biological Sciences - PJSIR, 2022)
A total of 2274 wheat seed samples were tested for Kamal bunt incidence during 1986-87 to 1991-92 by dry inspection method. Out of these, 1331 (58.53%) samples were found infected by Kamal bunt fungus (Tilletia indica). The highest infection percentage of Kamal bunt was found in Central Punjab (7.66%) and North West area of Pakistan (8.72%). On the basis of sample infection percentage, Rahim Yar Khan, Sukkur, Sakrand, Hyderabad and Quetta were the most suitable areas for the production of disease free quality seed. Comprehensive review regarding Kamal bunt investigation alongwith suggestions is given for planning effective disease management strategy. As the fungus has quarantine significance, domestic and international measures should be adopted to check its further spread.